Testing dynamic agency predictions to corporate finance - Silva, André Espozel Pinheiro da (2017)
This papers tests theoretical predictions concerning to agent compensation, debt structure and investment in the models of dynamic agency in DeMarzo and Fishman (2007), DeMarzo and Sannikov (2006) and DeMarzo, Fishman, He and Wang (2012). The results related to agent compensation are consistent with the patterns predicted in the models, indicating that the firm-years that the models would have as more likely to pay dividends are indeed the ones more likely to pay; also, among firms that pay dividends, more profits generate higher dividend payments and higher executive compensation, as predicted in the models. The prediction that firms that go well and reach a payment threshold present marginal q equal to average q, and thus after controlling for average q cash flows would not explain investment is also supported by the tests in here. On the other hand, predictions related to the role of the credit line and to the debt structure are not compatible with the results in here. The credit line doesn’t seem to be the provider of financial slack that protects the firm from low cash flows and also doesn’t seem to have the dynamics of being paid when profits are high and being more used when profits are low.